2018
DOI: 10.1002/term.2757
|View full text |Cite
|
Sign up to set email alerts
|

TuningForkhead Box D3overexpression to promote specific osteogenic differentiation of human embryonic stem cells while reducing pluripotency in a three‐dimensional culture system

Abstract: Clinical use of human embryonic stem cells (hESCs) in bone regeneration applications requires that their osteogenic differentiation be highly controllable as well as timeand cost-effective. The main goals of the current work were thus (a) to assess whether overexpression of pluripotency regulator Forkhead Box D3 (FOXD3) can enhance the osteogenic commitment of hESCs seeded in three-dimensional (3D) scaffolds and (b) to evaluate if the degree of FOXD3 overexpression regulates the strength and specificity of hES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In addition, FOX transcription factors have been shown to associate with cancer research such as drug resistance, tumor growth, genomic alterations or drivers of initiation and thought to be a potential therapeutic strategy to combat cancer and putative biomarkers for specific cancers [ 6 , 10 ]. The FOXD subfamily includes FOXD1 , FOXD2 , FOXD3 and FOXD4 and functions as a critical regulator in normal cell development and disease progression [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Moreover, the FOXD subfamily has also been found to play a role as an important regulator for tumorigenesis and cancer progression [ 19 , 20 , 21 , 22 , 23 , 24 ], e.g., therapeutic resistance and cancer metastasis, and serves as a prognostic biomarker in several types of cancer [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, FOX transcription factors have been shown to associate with cancer research such as drug resistance, tumor growth, genomic alterations or drivers of initiation and thought to be a potential therapeutic strategy to combat cancer and putative biomarkers for specific cancers [ 6 , 10 ]. The FOXD subfamily includes FOXD1 , FOXD2 , FOXD3 and FOXD4 and functions as a critical regulator in normal cell development and disease progression [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Moreover, the FOXD subfamily has also been found to play a role as an important regulator for tumorigenesis and cancer progression [ 19 , 20 , 21 , 22 , 23 , 24 ], e.g., therapeutic resistance and cancer metastasis, and serves as a prognostic biomarker in several types of cancer [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al pointed out that FoxD3 may mediate transcriptional activation of miR-496 triggered by IL-1β, thereby repressing the Wnt/ β-catenin signaling pathway and reducing osteoblast differentiation (Huang and Chen, 2017). Interestingly, a study by Kamaldinov et al showed that overexpressed FoxD3 may enhance osteogenesis in human embryonic stem cells via the endochondral ossification pathway (Kamaldinov et al, 2018).…”
Section: Fox Factors That Affect Osteogenic Differentiation Alone In Bone Metabolismmentioning
confidence: 99%